Atractylenolide-I Suppresses Tumorigenesis of Breast Cancer by Inhibiting Toll-Like Receptor 4-Mediated Nuclear Factor-κB Signaling Pathway - Long, Fangyi; Lin, Hong; Zhang, Xiqian; Zhang, Jianhui; Xiao, Hongtao; Wang, Ting (Frontiers in Pharmacology, 2020)
Background: Toll-like receptor 4 (TLR4) is an essential sensor related to tumorigenesis, and overexpression of TLR4 in human tumors often correlates with poor prognosis. Atractylenolide I (AT-I) is a major bioactive component from Rhizoma Atractylodes Macrocephalae. Emerging evidence suggests that AT-I exerts anti-tumor effects on various cancers such as colorectal cancer, bladder cancer and melanoma. Nevertheless, the effects of AT-I on mammary tumorigenesis remain unclear. Methods: In order to ascertain the correlation of TLR4/NF-κB pathway with breast cancer, the expression of TLR4 and NF-κB in normal breast tissues and cancer tissues with different TNM-stages was detected by human tissue microarray (TMA) and immunohistochemistry technology. The effects of AT-I on tumorigenesis were investigated by cell viability, colony formation, apoptosis, migration and invasion assays in two breast cancer cells (MCF-7 and MDA-MB-231), and N-Nitroso-N-methylurea (NMU) induced rat breast cancer models were developed to evaluate the anti-tumor effects of AT-I in vivo. The possible underlying mechanisms were further explored by western blot and ELISA assays after a series of LPS treatment and TLR4 knockdown experiments. Results: We found that TLR4 and NF-κB were significantly up-regulated in breast cancer tissues, and was correlated with advanced TNM-stages. AT-I could inhibit TLR4 mediated NF-κB signaling pathway and decrease NF-κB-regulated cytokines in breast cancer cells, thus inhibiting cell proliferation, migration and invasion, and inducing apoptosis of breast cancer cells. Furthermore, AT-I could inhibit NMU-induced rat mammary tumor progression through TLR4/NF-κB pathway. Conclusions: Our findings demonstrated that TLR4 and NF-κB were over expressed in breast cancer, and AT-I could suppress tumorigenesis of breast cancer via inhibiting TLR4-mediated NF-κB signaling pathway.